Inactivation efficacy and mechanisms of atmospheric cold plasma on Alicyclobacillus acidoterrestris: Insight into the influence of growth temperature on survival - Wang, Lang-Hong; Chen, Lin; Zhao, Siqi; Huang, Yanyan; Zeng, Xin-An; Aadil, Rana Muhammad (Frontiers in Nutrition, 2022)
The bactericidal effect of dielectric barrier discharge-atmospheric cold plasma (DBD-ACP, 20 and 30 kV) against Alicyclobacillus acidoterrestris on the saline solution and apple juice was investigated. Results show that DBD-ACP is effective for the inactivation of A. acidoterrestris by causing significant changes in cell membrane permeability and bacterial morphology. The effect of culture temperatures on the resistance of A. acidoterrestris to DBD-ACP was also studied. A. acidoterrestris cells grown at 25 ℃ had the lowest resistance but it was gradually increased as the culture temperature was increased (25-45 ℃) (p<0.05). Moreover, results from Fourier transform infrared spectroscopy (FT-IR) and Gas Chromatography-Mass Spectrometer (GC-MS) analysis showed that the increase in the culture temperature can gradually cause the decreased level of cyclohexaneundecanoic acid in the cell membrane of A. acidoterrestris (p<0.05). In contrast, cyclopentaneundecanoic acid, palmitic acid, and stearic acid showed an increasing trend in which the fluidity of the bacterial cell membrane decreased. This study shows a specific correlation between the resistance of A. acidoterrestris and the fatty acid composition of the cell membrane to DBD-ACP.